THEMATIC ROLE ASSIGNMENT IN ENGLISH SENTENCES: A QUICK GLANCE AT AN INTERFACE BETWEEN SYNTAX AND SEMANTICS - Eni Maharsi (Universitas PGRI Yogyakarta, 2015)
This paper examines the role of elements of English sentences by employing the approach ofthematic role assignment. The emphasis is on how the positioning of words and phrases insyntactic structure helps determine the roles that the referents of NPs play in the situationdescribed by the sentences. The results reveal that the position of an NP’s determines itsthematic role and. There is a relevance between deep syntactic structure and the assignmentof thematic roles for every NP in the sentence.